Taxation, growth and welfare: Dynamic effects of Estonia's 2000 income tax act - Michael Funke; Holger Strulik (Bank of Finland, Institute for Economies in Transition (BOFIT), 2003)
This paper analyses the long-run effects of Estonia s 2000 Income Tax Act with a dynamic general equilibrium model.Specifically, we consider the impact of the shift from an imputation system to one where companies only pay taxes on distributed profits.Balanced growth paths, transitional dynamics and welfare costs are computed. Our results indicate that the 2000 Income Tax Act leads to higher per capita income and investment, but lower welfare.A sensitivity analysis shows the results are rather robust.
URN:NBN:fi:bof-201408072205
Keywords: H25; H32; O41; O52; 330; growth; welfare; taxation; tax reform; Estonia